The Role of ASEAN Scholarships in Improving Access to Higher Education for Indonesian Students - Adasion, Fedro; Argenti, Gili (Jurnal Ilmiah Wahana Pendidikan, 2025)
The role of ASEAN scholarship programs in improving access to higher education for Indonesian students. Employing a qualitative descriptive approach through document analysis, the research identifies how these scholarships alleviate financial and non-financial barriers, thereby enhancing educational opportunities for students from diverse socio-economic backgrounds. The findings reveal that ASEAN scholarships not only provide comprehensive financial support but also foster regional integration by cultivating cross-cultural competencies and expanding academic networks. Despite these benefits, challenges remain in ensuring equitable access due to uneven information distribution, rigid selection criteria, and administrative inefficiencies. The study underscores the crucial roles of governmental, institutional, and private sector collaboration in optimizing scholarship implementation. Empirical evidence affirms that recipients of ASEAN scholarships achieve significant academic success and contribute to Indonesia’s human capital development, aligning with the ASEAN Socio-Cultural Community Blueprint 2025. This research contributes valuable insights for policymakers to enhance the inclusivity and effectiveness of scholarship programs in the ASEAN context.